COVID 19- Response from Education System (Indian Journal of Extension Education, 2020)
The world is facing numerous challenges caused by pandemic ‘COVID-19, one of them is facilitating to continue education. Avoiding physical closeness is the prime solution for human being to be saved from it, which cannot be possible in traditional education system followed in India. Though MHRD is guiding academic institute to have online classes which itself has proved a challenge due to lack of resources, less technical knowledge among teachers and taught supported by poor internet connection. To get an understanding about online education in University of Rajasthan, Jaipur, the present study was undertaken with the objective to explore the present status and challenges of online teaching-learning system during lock down along with an understanding of precaution to be taken after lock down (from the students point of view). Data was collected through Google form and the results show that three fourth respondents feels that education system cannot afford lock down, online classes can effectively meet the need of the students and they are interested in having online classes, but student union elections are not in their priority. Students emphasised the importance of physical classes.